Rabbit sperm cryopreservation: A review - Mocé, Eva; Vicente, José Salvador (2017)
Sperm cryopreservation is a great challenge, since many sperm are irreversibly damaged or present altered functionality after the whole process. Although components of extenders for sperm cryopreservation are quite similar between species, sperm from each of the species present peculiarities that force researchers to optimize the extenders and protocols for each particular species. In this review, information related to rabbit sperm cryopreservation is compiled. The topics discussed include the extenders and protocols developed for rabbit sperm cryopreservation, as well as fertility data obtained after artificial insemination with cryopreserved sperm and factors that may have an impact on the results obtained. In addition, suggestions for improving the results after cryopreservation of rabbit sperm are also proposed.